Impatiens baishaensis (Balsaminaceae): a new species from Sichuan, China - Ding, Bo; Wang, Jia-Cai; Deng, Hong-Ping; Wang, Chao-Ying (Phytotaxa, 2017)
Impatiens baishaensis B. Ding & H. P. Deng is a new species from Wawu Shan and Dafengding, Sichuan Province, China. The new species is superficially similar to I. oxyanthera in having 2-flowered racemose inflorescences and pink flowers with reddish veins, but differs from the latter by having smaller flowers, abaxial midveins of lateral sepals and dorsal petals puberulent, dorsal petal spotted with purple-red, and lower sepals navicular. Seed micromorphology and palynological features observed with scanning electron microscopy are also presented.